PENGEMBANGAN E-MODUL BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) PADA MATERI ALJABAR UNTUK SISWA KELAS VII SMP/MTS - Aprillia Benitha; Novaliyosi Novaliyosi (LPPM Universitas Bina Bangsa, 2022)
The purpose of this development is to produce a product in the form of mathematics teaching materials using a realistic mathematics education approach that is suitable for use by class VII students of SMPN 5 Serang City. The type of research used in this research is research and development (R&D). The development model used in this development research is the ADDIE model, which includes Analyze, Design, Development, Implementation, and Evaluate. The stage carried out by the researchers was only up to the implementation stage of small group trials to 12 students of class VII SMPN 5 Serang City then continued with the evaluation stage. The data collection instrument was in the form of a questionnaire. The questionnaire used is an expert validation questionnaire to assess the feasibility of the product and a student response questionnaire to assess the practicality of the product. The validation results obtained by the teaching materials developed were declared feasible with a presentation of 80% material expert validation, 85% media experts, and 82.5% education experts. The presentation of the results of the small group trial is with a percentage of 85%. Therefore it can be concluded that the product is feasible and practical to use